Performance enhancement analysis of an isolated DC-DC converter using fuzzy logic controller - Muthu Balaji, S.; Anand, R.; Senthil Pandian, P. (International Journal of Engineering and Technology, 2017)
High voltage gain dc-dc converters plays an major role in many modern industrialized applications like PV and fuel cells, electrical vehicles, dc backup systems (UPS, inverter), HID (high intensity discharge) lamps. As usual boost converter experiences a drawback of obtaining a high voltage at maximum duty cycle. Hence in order to increase the voltage gain of boost converter, this paper discusses about the advanced boost converter using solar power application. By using this technique, boost converter attains a high voltage which is ten times greater than the input supply voltage. The output voltage can be further increased to more than ten times the supply voltage by using a parallel capacitor and a coupled inductor. The voltage stress across the switch can be reduced due to high output voltage. The Converter is initially operated in open loop and then it is connected with closed loop. More over the fuzzy logic controller is used for the ripple reduction.